Acceleration Response First Passage Failure Probability Analysis Method for Nonlinear Package. (30th July 2018) - Zhu, Dapeng
Abstract : The acceleration response first passage failure problem of the nonlinear package base excited by Gaussian white noise is analyzed. The model correction factor method (MCFM) is implemented in conjunction with the first-order reliability method (FORM) to analyze the first passage failure probability of the nonlinear package. The white noise is discretized in standard normal space, and an iterative algorithm is proposed to find the design point of the packaging system. On the design point, the hypersurface representing the limit-state function of the nonlinear package is replaced approximately by a hyperplane representing the limit-state function of an equivalent linear system, and the FORM is employed to calculate the failure probability of the packaging system. The accuracy of this method is verified by crude Monte Carlo simulations. Numerical simulations are carried out to observe the effects of system parameters variations on failure probability which can be used for the improvement of packaging design.